2022
DOI: 10.1590/0004-282x-anp-2021-0133
|View full text |Cite
|
Sign up to set email alerts
|

Dialysis headache: characteristics, impact and cerebrovascular evaluation

Abstract: Background: Headache is one of the most frequent symptoms that occur during hemodialysis sessions. Despite the high prevalence of dialysis headache, it has been little studied. Objective: To evaluate the characteristics, impact and factors associated with dialysis headache. The behavior of the cerebral vasculature was also compared between patients with and without dialysis headache. Methods: This was a cross-sectional study. Consecutive patients who underwent hemodialysis were assessed through a semi-str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 25 publications
3
13
0
Order By: Relevance
“…This multifactorial nature of headache makes it difficult to assess. 9,11 Studies have shown that women have more risk factors for dialysis headache 9,11 , although no statistical relationship was found between dialysis headache and sex. 1,7,8,12 In our review, we found a predominance of dialysis headache in men (56.5% versus 43.5%), possibly because men more frequently undergo hemodialysis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This multifactorial nature of headache makes it difficult to assess. 9,11 Studies have shown that women have more risk factors for dialysis headache 9,11 , although no statistical relationship was found between dialysis headache and sex. 1,7,8,12 In our review, we found a predominance of dialysis headache in men (56.5% versus 43.5%), possibly because men more frequently undergo hemodialysis.…”
Section: Discussionmentioning
confidence: 99%
“…11 There is a significant decrease in plasma concentrations of CGRP after dialysis, thus, high values of this peptide may contribute to the onset of headache. 13 In turn, factors related to dialysis headache were associated with longer time in the hemodialysis program 9,12 and the frequency of sessions per week. 9 One study described that online haemodiafiltration (OL-HDF) had good results as a preventive method of dialysis headache.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although a common and debilitating experience in patients undergoing the procedure, little is known about its mechanisms. In this edition, Melo et al 2 is shedding some light in the understanding of this condition by studying 100 consecutive dialytic patients with structured questionnaires and transcranial doppler ultrasonography.…”
mentioning
confidence: 99%